Relations and working life of three generations of professionals in Cali-Colombia - Sánchez Salcedo, José Fernando (Sociedad y Economía, 2011)
In less than 10 years, professionals went from being one of the social groups more stable and protected work to become one of the most vulnerable. The change was due to the consequences generated by the implementation of the neoliberal policies which came to replace, from the decade of the 1990S, the old model of import substitution that had characterized the economies of the Latin American. This article is on the discontinuities and stays operated on the trajectories labor and relational of the three generations of professionals who have lived this process of change.